Towards automation and robotics in industrialised building system (IBS) : a literature review / Mohd Najib Abd Rashid … [et al.] - Abd Rashid, Mohd Najib; Abdullah, Mohd Rofdzi; Ismail, Dzulkarnaen; Mahyuddin, Muhammad Naim (2018)
The construction industry demands effective construction organisations, efficient construction processes and innovative construction techniques to effectively compete under increasing globalisation, market competition and technological advancements in the twenty-first century. The problems associated with construction such as decreasing quality and productivity, labour shortages, occupational safety, and inferior working conditions have opened the possibility of more revolutionary solutions within the industry. One of the prospective options is in the implementation of innovative technologies in construction such as automation and robotics is through the Industrialised Building System (IBS), which has the potential to improve the industry in terms of productivity, safety and quality. This is the review paper describe on the potential used of Automation and Robotics through Industrialised Building System as well as to adopt the concept of Industrilisation towards the better future of Malaysian Construction Industry.